Resistance to Seawater of a New Cement Mortar Based on Additions of Recycled Product - Harbi, Radhia; Derabla, Riadh; Nafa, Zahreddine (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper aims to explore some sustainability indicators including mainly the resistance to seawater of mortars containing 5% kaolin filler in the sand and different types of ecoproducts as cement additions. To this end, an experimental study was carried out with the aim of evaluating the effects of three types of cement additions (glass powder (GP), metakaolin (MK) and brick waste (BW)) with contents of 5, 15 and 25% as well as binary and ternary combinations of these same additions.
Keywords: cement mortar; recycled products; additions to cement; durability; ecoproduct; brick; glass powder; kaolin filler; zaprawa cementowa; dodatek do cementu; produkty recyklingu; mączka szklana; wypełniacz kaolinowy; trwałość; odporność na wodę morską